Geophysical investigation of glass 'hotspots' in glass dumps as potential secondary raw material sources. (1st April 2020) - Mutafela, Richard Nasilele; Lopez, Etzar Gomez; Dahlin, Torleif; Kaczala, Fabio; Marques, Marcia; Jani, Yahya; Hogland, William
Highlights: Waste mixing during glass dump excavation jeopardizes resource recovery potential. ERT can detect glass hotspots for careful excavation to avoid costly waste sorting steps. Glass and bedrock resistivity similarities require caution when interpreting ERT data. Resistivity discrepancies introduce artifacts, causing increased uncertainty with depth. ERT is applicable to glass dumps given their shallowness (less uncertainty near surface). Abstract: This study investigates the potential for Electrical Resistivity Tomography (ERT) to detect buried glass 'hotspots' in a glass waste dump based on results from an open glass dump investigated initially. This detection potential is vital for excavation and later use of buried materials as secondary resources. After ERT, test pits (TPs) were excavated around suspected glass hotspots and physico-chemical characterisation of the materials was done. Hotspots were successfully identified as regions of high resistivity (>8000 Ωm) and were thus confirmed by TPs which indicated mean glass composition of 87.2% among samples (up to 99% in some). However, high discrepancies in material resistivities increased the risk for introduction of artefacts, thus increasing the degree of uncertainty with depth, whereas similarities in resistivity between granite bedrock and crystal glass presented data misinterpretation risks. Nevertheless, suitable survey design, careful field procedures and caution exercised by basing data interpretations primarily on TP excavation observations generated good results particularly for near-surface materials, which is useful since glass waste dumps are inherently shallow. Thus, ERT could be a useful technique for obtaining more homogeneous excavated glass and other materials for use as secondary resources in metal extraction and other waste recycling techniques while eliminating complicated and often costly waste sorting needs.